A long-term high-fat diet influences brain damage and is linked to the activation of HIF-1α/AMPK/mTOR/p70S6K signalling - Chen, Fei; Yi, Wen-min; Wang, Sheng-yuan; Yuan, Ming-hao; Wen, Jie; Li, Hong-Yan; Zou, Qian; Liu, Shu; Cai, Zhi-you (Frontiers in Neuroscience, 2022)
High-fat diets (HFDs) are related to the incidence of obesity and diabetes, but the effect of high-fat diet-induced brain damage remains to be clarified. In our study, we found that 24 weeks of HFD feeding effectively induced obesity and a change in fur colour in mice. In addition, the mice also exhibited deficits in learning and memory. We further found that autophagic flux was impaired in mice after HFD feeding. Hypoxia-inducible factor 1α (HIF-1α) expression was significantly increased in HFD-fed mice, and HFD feeding inhibited Adenosine monophosphate-activated protein kinase (AMPK) phosphorylation and induced mechanistic target of rapamycin (mTOR)phosphorylation and p70S6K expression. A HFD-induced BV2 cell model was treated with palmitic acid (PA) and used to further verify a similar result. We concluded that improving tissue hypoxia or enhancing autophagy through the AMPK/mTOR/p70S6K pathway may be a relevant strategy for improving obesity- and ageing-related disorders.